Instilling Aswaja An-Nahdliyah Values In Shaping Santri Religious Moderation - kuni Badriah; Ubaidillah Ubaidillah; Abd. Muhith; Samsul Arifin (Institut Agama Islam An-Nawawi Purworejo, 2023)
The cultivation of tawassuth, i'tidal, tasamuh, and tawazun values is the basis for forming religious moderation. The phenomenon that often occurs today is an attitude of intolerance, radicalism that not only occurs in society in general, but one of the attitudes or behaviors of radicalism also begins to infiltrate the pesantren environment. So it is very important, the cultivation of the values of religious moderation. This study aims to determine the values in religious moderation at Nurut Tholabah Islamic Boarding School. This research methodology uses qualitative research methods, combining data collection techniques by observation, interviews, and documentation. The results of this study found that the cultivation of Nahdlatul Ulama values in shaping the religious moderation attitude of students through exemplary attitudes, and teaching from kyai, teachers, and pesantren administrators, so that students in everyday life can respect, respect fellow students, and when socializing in the general community.id